Analysis of the mechanism of state regulation of innovative projects in the regions of the Republic of Kazakhstan. (Journal of Economic Research & Business Administration, 2016)
The main priority areas of science in Almaty is possible to determineareas such as nuclear science, biomedical science and technology researchin the field of natural resources, agricultural science and technology, environmentalprotection and others. Innovative development of economyof the country is now the basis of the state policy of Kazakhstan, which isaimed at creating the economic conditions for production of competitivehigh-tech products. This article analyzes the mechanism of state regulationof innovative projects in the regions of Kazakhstan. To better support thenew policy, the State should take the example of the benefits provided bythe industrialized countries. Also believes that instruments to support innovationactivities include tax incentives for activities of regional technologyparks and EPZs.region; innovation; design innovation; government regulation
Keywords: region; innovation; design innovation; government regulation